Causa Materialis Pancasila Menurut Notonagoro - Amien, Miska (Jurnal Filsafat "WISDOM", 2006)
In investigating the original cause of Pancasila, ProfessorNotonagoro involved the use of causality theory. Based on thecausality theory, Pancasila’s causa materialis originated fromtraditions, cultures and religions belonged to Indonesia. The traditionshere are in the sense of their relation to the social, economics,politics and state structure problems. But it is important to befirmed here that the traditions can be transformed into sila-silaPancasila even thought not at all. Causa materialis of Pancasila originated from Indonesiancultures involve everything which was produced by human mindsuch as science, technology, economics, art, etc. Because of theunderstanding of culture are determined by the scientific point ofview, in this case, the local cultures of Indonesia which were takenas sila-sila Pancasila have not been explained here. In addition, causa materialis of Pancasila originated fromreligions can be expressed throughout the reality of Indonesian asreligious people who acknowledged the Great Unity of God. Thisdivinity principle tends to show that Indonesian people believe inGod. More than this, each Indonesian people believe in God on thebase of their religion and faith.